Nucleon Emission Number as a Probe of Isospin-Dependent N-N Cross Section in Photonuclear Reactions - 郭文军 黄江伟 雍高产 张霄吉 张傲 (Chinese physics letters, 2014)
Based on the modified isospin-dependent quantum molecular dynamics model, the number of emitted nucleons in a photonuclear reaction is studied with different symmetry potentials and different isospin-dependent nucleonnucleon （N N） collision cross sections. It is found that the number of emitted nucleons is sensitive to the isospin-dependent nucleon-nucleon cross section when the photon＇s energy is higher than 150 MeV, while it is insensitive to symmetry potential. The number of emitted neutrons is more sensitive to N N collision cross sections than that of protons. It is realized that the number of emitted neutrons can be used as a sensitive probe to extract the information of the isospin-dependent N N cross section at high energy photonuclear reactions.